High rate of persistent HPV detection after diagnostic cervical excision in older screen‐positive women - Gustafson, Line Winther; Krog, Louise; Sardini, Bayan; Tranberg, Mette; Petersen, Lone Kjeld; Andersen, Berit; Bor, Pinar; Hammer, Anne (Acta obstetricia et gynecologica Scandinavica, 2025)
Introduction Diagnostic work‐up of older women with a positive cervical cancer screening test is often challenging due to incomplete visualization of the transformation zone. To reduce the risk of missing disease, a diagnostic cervical excision may be performed. However, little is known on treatment efficacy and post‐treatment surveillance for older women. We aimed to investigate the proportion of women testing negative for human papillomavirus (HPV) following a diagnostic cervical excision due to an abnormal screening test. Material and Methods We conducted a prospective cohort study on women aged ≥45 years who were referred for colposcopy due to an abnormal screening test between March 2019 and June 2021. All women had incomplete visualization of the transformation zone and underwent colposcopy and a diagnostic cervical excision at the first visit. Women were followed from date of excision until January 30, 2023. Follow‐up data was retrieved from the Danish Pathology Databank, and baseline characteristics were obtained from medical records. Cox regression was used on interval‐censored data to estimate crude and adjusted hazard ratios for a negative HPV test after cervical excision, stratified by histology and age. Results A total of 100 women underwent a diagnostic cervical excision and had at least one HPV test during follow‐up. Median age was 67.4 years, and median follow‐up time was 2.9 years. At the end of follow‐up, 70% tested HPV negative. Women with cervical intraepithelial neoplasia grade two or worse in their excision specimen were more likely to test HPV negative at the first test after cervical excision compared to women with less than cervical intraepithelial neoplasia grade two, however, not statistically significant (adjusted hazard ratio 1.69, 95% CI 0.92–3.10). Women aged 65–84 years were less likely to test HPV negative compared to women <65 years (adjusted hazard ratio 0.49, 95% CI 0.28–0.87). Conclusions In older women undergoing a diagnostic cervical excision, 70% tested HPV negative after 2.9 years, leaving 30% with persistent HPV positivity. More studies are needed to determine the risks associated with continued HPV positivity in the absence of high‐grade disease. Furthermore, given the absence of specific guidelines, the optimal surveillance frequency remains unknown. Among older women monitored for 2.9 years after a diagnostic cervical excision, 70% tested negative for HPV. Consequently, 30% continued to test positive and remained in follow‐up. The optimal surveillance frequency and methods for these women remain uncertain.